Reformulation of Regulations in the Context of Structuring the Indonesian Maritime Security Regime - Gita Prissandi; Surya Wiranto; Budiman Djoko Said; Pujo Widodo; Herlina Juni Risma Saragih; Panji Suwarno (CV. AFDIFAL MAJU BERKAH, 2023)
This article discusses the reformulation of regulations in the context of structuring the Indonesian maritime security regime. The research employs a qualitative method using secondary data sources obtained through a literature review. The specific background of problems addressed in this research includes issues related to IUU fishing and other maritime security threats faced by Indonesia. The main problem addressed is the lack of cross-sectoral coordination and frequent differences in perception of authority among law enforcement agencies at sea. The research objective is to examine how restructuring Indonesia's maritime security regime can be achieved through reformulation of overlapping regulations and harmonization of authority among maritime security agencies. The article concludes that the restructuring of Indonesia's maritime security regime can be achieved through these measures.